Scope and application - Long, David (Henry Stewart Talks, 2012)
Research, Development, Stages and regulations of R&D, Good "X" practice (GXP), GLP targeting non-clinical safety studies, Non-clinical health and environmental safety tests, Minimum phase I and II clinical trial duration, Minimum phase III clinical trial requirements, Safety studies design